Hi,

I did it four times and it looks worse now.

Does anyone see what I did wrong?

This is what I did:

Integral x^2cosmx dx

u=cosmx

dv=x^2dx

du=-sinmx

v=x^3/3

integral x^2cosmx dx=(cosmx)(x^3/3)-integral(x^3/3(cosmx)

then I did it again:

u=x^3

dv=cosmx dx

du=2x^2/3 (quotient rule)

v=sinmx

(x^3)/3(sinmx)-integral(sinmx)(2x^2/3)

so...(cosmx)(x^3/3)-(x^3/3)(sinmx)-integral sin(mx)(2x^2/3)

then I did it again

u=2x^2/3

dv=sinmx

du=4/3x

v=-cosmx

(cosmx)(x^3/3)-(x^3)/3(sinmx)-(2x^2/3)(-cosmx)-integral (-cosmx)4/3x

then I simplified

(cosmx)(x^3/3)-(x^3/3)(sinmx)+(2x^2/3)cosmx-integral -cosmx(4/3x)

then I did it again

u=2x^2/3

dv=cosmx

du=12x+2x^2/3(-sinmx)/9 (this doesn't look like its going to help)

v=sinmx

Thank you very much